Polyionic liquid derived carbon coated metal catalyst and preparation and application thereof
By forming a polyionic liquid-derived carbon cladding layer on the surface of the metal catalyst, the problem of insufficient catalyst activity and selectivity is solved, and the efficiency, selectivity and stability of the catalytic hydrogenation reaction is achieved, and the value of industrial application is enhanced.
Patent Information
- Application Number
- CN202411683323.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art has problems of weak catalyst activity, low selectivity and poor stability in catalytic chlorinated nitrobenzene hydrogenation reaction, resulting in low production efficiency and excessive side reactions.
Polyionic liquid-derived carbon-coated metal catalyst is used, which increases the activity and selectivity of the catalyst by in-situ polymerization on the metal surface and increases the binding energy by nitrogen doping.
The catalytic hydrogenation reaction is achieved with high activity, selectivity and stability, reducing the generation of by-products, and improving the reuse rate of catalysts and industrial application value.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a polyionic liquid derived carbon coated metal catalyst and its preparation and application in catalytic hydrogenation reaction of chloronitrobenzene. Background Art
[0002] Chloroaniline is a colorless to light yellow oily liquid, and is the raw material of the herbicide chlorsulfuron. In the dye industry, it is an important dye intermediate, used as the color base of ice dye; it can also be used as the diazo component of azo dyes, used in the production of acid black, acid blue and organic lakes such as water-fast yellow R, permanent red FR, and Hansa yellow HR. It can also be used to prepare crosslinking agents for medicines, pesticides, and polyurethane resins. Methyldichloroaniline is an important organic intermediate in the field of fine chemicals.
[0003] At present, the industrial process for preparing chloroaniline is mainly based on catalytic hydrogenation reduction of the corresponding chloronitrobenzene. The reaction mechanism is shown below.
[0004]
[0005] Hydrogenation Mechanism of Chloronitrobenzene
[0006] The hydrogenation of halogenated nitro compounds is a relatively complex chemical reaction process, including parallel reactions and serial reactions, which may generate different hydrogenation intermediates. As shown above, there are two different reaction routes for the hydrogenation of chloronitrobenzene. Chloronitrobenzene generates chlorophenylhydroxylamine under the action of hydrogen, and then dehydrates to generate chloroaniline. If the catalyst activity is strong, it will lead to excessive hydrogenation and further dechlorination to generate aniline or chlorobenzene.
[0007] At present, the processes reported for the production of chloroaniline are mainly listed below: the iron chip reduction method is mature, simple, and easy to control in production, but this method has problems such as large equipment, large amount of reaction heat that is difficult to recover, large iron powder consumption, difficulty in achieving continuous production, slow reaction speed and difficulty in product separation, and low production efficiency; the alkali sulfide reduction method is a method currently used by most companies to produce chloroaniline. Compared with the iron chip reduction method, the reaction conditions are relatively mild and the products are easy to separate, but the problem of alkali solution polluting the environment is more serious, the cost is high, and the yield is low; the electrochemical reduction method is environmentally friendly and has mild reaction conditions, but it needs to overcome problems such as high energy consumption, diaphragm life and electrode activity; and the catalytic hydrogenation reduction method is relatively green and clean, with a simple process and not easy to cause a large amount of acid and alkali solution emissions. It is one of the most popular methods at present, but this method has a dechlorination side reaction, so improving the catalyst performance to improve the selectivity of the reaction has received widespread attention.
[0008] Coated catalysts use coatings to wrap active substances inside and form a protective film outside. This coating can not only protect the catalyst from the influence of the external environment, resist the erosion of high temperature, high pressure and corrosive substances, prevent the agglomeration and loss of metal nanoparticles, and extend the service life of the catalyst, but also can precisely control the reaction activity and selectivity of the catalyst by regulating the thickness, composition and structure of the coating, thereby improving the efficiency of the catalytic reaction and the purity of the product.
[0009] Ionic liquids (ILs) have been shown to be effective in improving the stability of metal nanoparticles. The protective layer introduced by ILs provides electrostatic protection against aggregation. However, there are no reports on the use of ILs to enhance the stability of SACs without compromising activity. Considering the remarkable success of ILs in NP and homogeneous catalysis, we propose that IL-induced electrostatic stabilization may be a viable strategy to enhance the stability of single-atom catalysts. We also envision that electronic modification of isolated metal atoms by charged cations or anions may lead to improvements in catalytic activity and selectivity.
[0010] In summary, it is urgent to find a highly dispersed, highly active, highly selective and highly stable coated catalyst for catalytic hydrogenation systems. Summary of the invention
[0011] One of the purposes of the present invention is to provide a method for preparing a polyionic liquid derived carbon-coated metal catalyst, wherein the catalyst is provided with a nitrogen-doped carbon layer by poly 1-ethyl-3-vinylimidazole nitrate, which not only provides protection for the active center, but also the conductive properties provided by the poly 1-ethyl-3-vinylimidazole nitrate derived carbon layer itself promote electron transport between carbon layers.
[0012] A second object of the present invention is to provide a polyionic liquid derived carbon-coated metal catalyst.
[0013] The third object of the present invention is to provide the use of the polyionic liquid derived carbon-coated metal catalyst in the catalytic hydrogenation reaction of chloronitrobenzene, and the catalyst has excellent activity, selectivity and stability.
[0014] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0015] In a first aspect, the present invention provides a method for preparing a polyionic liquid-derived carbon-coated metal catalyst, which is carried out according to the following steps:
[0016] Step 1: dissolving activated carbon and azobisisobutyronitrile (AIBN) in a mixed solution of ethanol and water, blowing nitrogen gas to deoxygenate, and obtaining an activated carbon / AIBN suspension;
[0017] Step 2: under vigorous stirring, adding the deoxygenated hexahydrate chloroplatinic acid ethanol solution dropwise to the suspension obtained in step 1 to obtain an activated carbon / AIBN suspension loaded with platinum;
[0018] Step 3: dissolving 1-ethyl-3-vinylimidazole nitrate in a mixed solution of ethanol and water, slowly adding the solution to the activated carbon / AIBN suspension loaded with platinum obtained in step 2 after deoxygenation, stirring and polymerizing at 60-70° C. for 12-24 hours under nitrogen protection, and filtering to obtain a polymerized ionic liquid-modified activated carbon-loaded platinum catalyst precursor; the weight ratio of the activated carbon to 1-ethyl-3-vinylimidazole nitrate in the activated carbon / AIBN suspension loaded with platinum is 1:0.2-1;
[0019] Step 4: drying the activated carbon-supported platinum catalyst precursor modified by the polymerized ionic liquid obtained in step 3;
[0020] Step 5: The product obtained in step 4 is first calcined under a hydrogen atmosphere and then calcined under an inert gas atmosphere. The resulting product is a polyionic liquid-derived carbon-coated metal catalyst, named M / C@PIL-XY, where "M" represents metal, "X" represents hydrogen calcination temperature, "Y" represents inert gas calcination temperature, "@" represents coating, " / " represents loading, and "PIL" represents polyionic liquid.
[0021] The 1-ethyl-3-vinylimidazole nitrate described in the present invention can be prepared with reference to the literature [Gao J, Cao J, Yin Z, et al. A Facilitate Process to Prepare Hydrophilic Ionic Liquid Monomers Free Of Halide Impurity and Their Electrochemical Properties. [J]. International Journal of Electrochemical Science, 2013, 8: 4914–4923.].
[0022] Preferably, in step 1, the mass ratio of activated carbon to AIBN is 1:0.005-1, more preferably 1:0.005-0.01.
[0023] Preferably, in step one or three, the volume ratio of ethanol to water in the mixed solution of ethanol and water is 10:6-10, more preferably 10:7.
[0024] Preferably, in step 2, the concentration of the chloroplatinic acid hexahydrate ethanol solution is 0.05-0.15 g / mL, more preferably 0.1 g / mL.
[0025] Preferably, in step 2, the mass fraction ratio of platinum to activated carbon in the hexahydrate chloroplatinic acid ethanol solution is 2.5-3.5%:1, more preferably 3%:1.
[0026] Preferably, in step three, the weight ratio of the activated carbon to 1-ethyl-3-vinylimidazole nitrate is 1:0.6.
[0027] Preferably, in step 4, the drying conditions are: drying temperature is 60-80° C., and drying time is 8-12 hours.
[0028] Preferably, in step five, the heating rate is 10°C / min, the hydrogen reduction condition is 100-200°C for 2h, and the N2 calcination condition is 450-500°C for 2h.
[0029] In a second aspect, the present invention provides a polyionic liquid-derived carbon-coated metal catalyst prepared according to the preparation method described in the first aspect.
[0030] In a third aspect, the present invention provides the use of the polyionic liquid-derived carbon-coated metal catalyst in the catalytic hydrogenation reaction of chloronitrobenzene.
[0031] The chloronitrobenzene described in the present invention is specifically one of the following:
[0032]
[0033] O-chloronitrobenzene is preferred.
[0034] Preferably, the application is as follows: adding chloronitrobenzene, a solvent and a polyionic liquid derived carbon-coated metal catalyst into a high-pressure reactor, passing nitrogen to remove air, and then passing hydrogen to stir the reaction to generate chloroaniline.
[0035] Preferably, the solvent is ethanol.
[0036] Preferably, the mass amount of the polyionic liquid derived carbon-coated metal catalyst is 1-5% of the mass of chloronitrobenzene, and most preferably 2-3%.
[0037] Preferably, the mass volume ratio of the chloronitrobenzene to the solvent is 10 g: (50-100) mL.
[0038] Preferably, the hydrogen pressure is maintained at 0.7-1.2 MPa, more preferably at 1.0 MPa, and the reaction temperature is controlled at 60-70°C, optimally at 70°C.
[0039] Preferably, the stirring rate is 500-1000 rpm.
[0040] Compared with the prior art, the invention has the following advantages:
[0041] (1) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention uses a polymer polyionic liquid as the carbon and nitrogen source of the shell layer, applies the polyionic liquid to a thermal catalytic reaction, and increases the binding energy of metal atoms by nitrogen doping, thereby increasing the catalyst activity.
[0042] (2) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention is in situ polymerized on the metal surface and completely coats the metal, thereby bypassing the problem of weak binding force between the ionic liquid and the metal surface. The polyionic liquid is applied in a disguised manner. Different from the partial coating of mesoporous catalysts, the preparation method is simple and the application of polyionic liquid is more efficient.
[0043] (3) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention uses AIBN as a free radical initiator during the preparation process, which not only makes 1-ethyl-3-vinylimidazole nitrate more easily adhere to the metal surface, polymerizes in situ on the metal surface and achieves full coating, but also helps the contact of 1-ethyl-3-vinylimidazole nitrate in the solution, thereby increasing the polymerization efficiency.
[0044] (4) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention uses a method of directly introducing graphitic nitrogen to regulate the activity of the catalyst. The content of graphitic nitrogen in the catalyst can be regulated by adjusting the calcination temperature, thereby affecting the catalyst activity.
[0045] (5) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention has a polyionic liquid carbon layer completely coated on the metal surface, which assists the electron transfer between the inner core active metal and the reaction substrate, making the catalyst highly active; the outer shell layer protects the inner core metal, preventing single atoms from agglomerating, and making the catalyst highly stable.
[0046] (6) The polyionic liquid-derived carbon-coated metal catalyst provided by the present invention is applied to a catalytic hydrogenation system, and the hydrogenation of chloronitrobenzene to generate chloroaniline is selected as a probe reaction. The generated by-products are small, the selectivity is high, and the corrosion to the equipment is reduced. The catalyst has good stability and can be reused many times. At the same time, it is highly safe during use and has high industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1a , Figure 1b , Figure 1c They are TEM images of Pt / C (model: T3EQ1, Shaanxi Ruike New Materials Co., Ltd.), Pt / C@IL-150-500 (Comparative Example 2), and Pt / C@PIL-150-500 (Example 1). DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way.
[0049] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0050] The coconut shell activated carbon used in the embodiment of the present invention was purchased from Chengde Tianyuan Activated Carbon Co., Ltd., with a specification of 20-40 mesh and an iodine value of 1000; the platinum solution was all chloroplatinic acid hexahydrate ethanol solution.
[0051] Comparative Example 1: Preparation method of poly 1-ethyl-3-vinyl imidazole nitrate
[0052] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0053] 0.6 g of 1-ethyl-3-vinylimidazole nitrate was dissolved in 17 mL of a solution of ethanol and water in a mixed volume ratio of 10:7. After deoxygenation, 0.006 g of AIBN was added, and polymerization was carried out at 65° C. under nitrogen protection for 24 h to obtain poly 1-ethyl-3-vinylimidazole nitrate.
[0054] Example 1
[0055] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0056] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL chloroplatinic acid hexahydrate ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain an activated carbon / AIBN suspension loaded with platinum. 0.6g 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-supported platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the temperature was switched to nitrogen, and the temperature was raised from 150°C to 500°C at 10°C / min, and the nitrogen was calcined for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@PIL-150-500.
[0057] Example 2
[0058] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0059] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain an activated carbon / AIBN suspension loaded with platinum. 0.2g of 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-supported platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the temperature was switched to nitrogen, and the temperature was raised from 150°C to 500°C at 10°C / min, and the nitrogen was calcined for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@PIL-150-500.
[0060] Example 3
[0061] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0062] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain an activated carbon / AIBN suspension loaded with platinum. 0.4g of 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-supported platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the temperature was switched to nitrogen, and the temperature was raised from 150°C to 500°C at 10°C / min, and the nitrogen was calcined for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@PIL-150-500.
[0063] Example 4
[0064] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0065] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain an activated carbon / AIBN suspension loaded with platinum. 0.8g of 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-supported platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the temperature was switched to nitrogen, and the temperature was raised from 150°C to 500°C at 10°C / min, and the nitrogen was calcined for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@PIL-150-500.
[0066] Example 5
[0067] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0068] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain an activated carbon / AIBN suspension loaded with platinum. 1g of 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of a solution of ethanol and water in a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-supported platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the temperature was switched to nitrogen, and the temperature was raised from 150°C to 500°C at 10°C / min, and the nitrogen was calcined for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@PIL-150-500.
[0069] Comparative Example 2: No free radical initiator added
[0070] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0071] 1g coconut shell activated carbon was dissolved in 17mL of ethanol and water solution with a volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon suspension under vigorous stirring at 800rpm to obtain an activated carbon suspension loaded with platinum. 0.6g of 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of ethanol and water solution with a volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon suspension loaded with platinum, polymerized at 65°C for 24h under nitrogen protection, and filtered to obtain a polymerized ionic liquid-modified activated carbon-loaded platinum catalyst precursor. The precursor was dried at 80°C for 8 hours, and then placed in a tubular furnace and introduced with hydrogen. The temperature was raised from room temperature to 150°C at 10°C / min, and the hydrogen was reduced for 2 hours. Then, the precursor was switched to nitrogen and continued to be heated from 150°C to 500°C at 10°C / min, and the precursor was calcined with nitrogen for 2 hours. The polyionic liquid-derived carbon-coated metal catalyst was obtained, which was recorded as Pt / C@IL-150-500.
[0072] TEM images of Pt / C@PIL-150-500 prepared in Example 1, commercial Pt / C (model: T3EQ1, Shaanxi Ruike New Materials Co., Ltd.) and Pt / C@IL-150-500 prepared in Comparative Example 2 are shown in FIG. Figure 1c , Figure 1a and Figure 1b As shown, Pt / C is a typical uncoated supported metal catalyst structure with obvious metal nanoparticles. No obvious coating layer is observed on the metal nanoparticles in Pt / C@IL-150-500, while the metal particles in Pt / C@PIL-150-500 are completely coated, indicating that Pt / C@PIL-150-500 is a coated catalyst.
[0073] Comparative Example 3: No Hydrogen Reduction
[0074] In an ice bath, 4.0956 g of diethyl sulfate was added dropwise to 2.5 g of vinyl imidazole, and stirred at 800 rpm for 3 h. The solution after the reaction was added dropwise to an ethanol solution in which 2.2358 g of KOH was dissolved, and stirred vigorously for 0.5 h, and then filtered to obtain a clear filtrate. Dilute nitric acid in an amount equimolar to KOH was added dropwise to the solution, and the filtrate was filtered after stirring for 0.5 h. The filtrate was rotary evaporated to obtain a light yellow viscous liquid, and then washed with 10 ml of ether 3 times, and vacuum dried at 40 ° C for 24 h to obtain 1-ethyl-3-vinyl imidazole nitrate.
[0075] 1g coconut shell activated carbon and 0.006g AIBN were dissolved in 17mL of ethanol and water solution with a mixed volume ratio of 10:7, nitrogen was blown to deoxygenate, and 797μL of 0.1g / mL hexahydrate chloroplatinic acid ethanol solution was added dropwise to the activated carbon / AIBN suspension under vigorous stirring at 800rpm to obtain activated carbon / AIBN suspension loaded with platinum. 0.6g 1-ethyl-3-vinyl imidazole nitrate was dissolved in 17mL of ethanol and water solution with a mixed volume ratio of 10:7, and after deoxygenation, it was slowly added to the activated carbon / AIBN suspension loaded with platinum, polymerized at 65℃ for 24h under nitrogen protection, and filtered to obtain the activated carbon supported platinum catalyst precursor modified by polymerized ionic liquid. After the precursor was dried at 80℃ for 8h, it was placed in a tubular furnace and nitrogen was passed through, and the temperature was raised from room temperature to 500℃ at 10℃ / min, and nitrogen was roasted for 2h. The polyionic liquid-derived carbon-coated metal catalyst was prepared and recorded as Pt / C@PILs-X-500.
[0076] Application Example 1
[0077] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Example 1, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0078] Application Example 2
[0079] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Example 2, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0080] Application Example 3
[0081] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Example 3, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0082] Application Example 4
[0083] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Example 4, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0084] Application Example 5
[0085] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Example 5, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0086] Table 1 Comparison of catalyst performance in Examples 1 to 5
[0087]
[0088]
[0089] Application Example 6
[0090] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Comparative Example 2, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0091] Application Example 7
[0092] In a 250mL high-pressure reactor, 0.2g of the polyionic liquid-derived carbon-coated metal catalyst prepared in Comparative Example 3, 9.42g of o-chloronitrobenzene and 80mL of ethanol were added in sequence, the reactor was sealed, and the air in the reactor was exhausted three times with nitrogen. The nitrogen in the reactor was repeatedly replaced with hydrogen for 5 times, and then the hydrogen pressure in the reactor was adjusted to 1MPa. After heating to 70°C, stirring (stirring rate was 750rpm) was started to start the reaction; after the reaction was completed, when the temperature in the reactor dropped to room temperature, 2.04396g of n-dodecane was added as an internal standard, stirred for 1min, sampled, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the solvent was filtered out under reduced pressure, washed with deionized water and methanol, and dried to obtain the target product.
[0093] Table 2 Comparison of catalyst performance of Examples 1, 6 and 7
[0094]
[0095] The comparison between Example 1 and Comparative Example 2 shows that the use of AIBN as a free radical initiator in the catalyst preparation process is conducive to the in-situ polymerization of 1-ethyl-3-vinylimidazole nitrate on the surface of metal particles to form a polyionic liquid and achieve full coverage of the metal particles, thereby improving the catalytic hydrogenation performance of the catalyst. The comparison between Example 1 and Comparative Example 3 shows that after Pt is reduced with hydrogen, the Pt 2+ and Pt 4+ Transformed into Pt 0 , which greatly improves the activity of the catalyst.
[0096] Application Example 8
[0097] The experimental conditions were the same as those in Application Example 1, and the catalyst obtained by filtration was repeatedly used in the next reaction. The composition of the hydrogenation product in the filtrate obtained in each application experiment was analyzed by high performance gas chromatography, and the results are shown in Table 2:
[0098] Table 3 Catalyst Example 1 Application Results
[0099]
[0100] *Reaction conditions are the same as those in Application Example 1
[0101] Application Example 9
[0102] The experimental conditions were the same as those in Application Example 3, and the catalyst obtained by filtration was repeatedly used in the next reaction. The composition of the hydrogenation product in the filtrate obtained in each application experiment was analyzed by high performance gas chromatography, and the results are shown in Table 3:
[0103] Table 4 Catalyst Comparative Example 3 Application Results
[0104]
[0105] *The reaction conditions are the same as those in Application Example 3.
Claims
1. A method for preparing a polyionic liquid-derived carbon-coated metal catalyst, characterized in that: The preparation method is carried out according to the following steps: Step 1: dissolving activated carbon and azobisisobutyronitrile in a mixed solution of ethanol and water, blowing nitrogen gas to deoxygenate, and obtaining an activated carbon / AIBN suspension; Step 2: under vigorous stirring, adding the deoxygenated hexahydrate chloroplatinic acid ethanol solution dropwise to the suspension obtained in step 1 to obtain an activated carbon / AIBN suspension loaded with platinum; Step 3: dissolving 1-ethyl-3-vinylimidazole nitrate in a mixed solution of ethanol and water, slowly adding the solution to the activated carbon / AIBN suspension loaded with platinum obtained in step 2 after deoxygenation, stirring and polymerizing at 60-70° C. for 12-24 hours under nitrogen protection, and filtering to obtain a polymerized ionic liquid-modified activated carbon-loaded platinum catalyst precursor; the weight ratio of the activated carbon to 1-ethyl-3-vinylimidazole nitrate in the activated carbon / AIBN suspension loaded with platinum is 1:0.2-1; Step 4: drying the activated carbon-supported platinum catalyst precursor modified by the polymerized ionic liquid obtained in step 3; Step 5: calcine the product obtained in step 4 in a hydrogen atmosphere first, and then in an inert gas atmosphere, to obtain a polyionic liquid-derived carbon-coated metal catalyst.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of activated carbon to AIBN is 1:0.005-1, preferably 1:0.005-0.
01.
3. The preparation method according to claim 1, characterized in that: In step 1 or step 3, the volume ratio of ethanol to water in the mixed solution of ethanol and water is 10:6-10.
4. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the hexahydrate chloroplatinic acid ethanol solution is 0.05-0.15 g / mL.
5. The preparation method according to claim 1, characterized in that: In step 2, the mass fraction ratio of platinum to activated carbon in the hexahydrate chloroplatinic acid ethanol solution is 2.5-3.5%:
1.
6. The preparation method according to claim 1, characterized in that: In step 3, the weight ratio of the activated carbon to 1-ethyl-3-vinylimidazole nitrate is 1:0.
6.
7. The preparation method according to claim 1, characterized in that: In step 4, the drying conditions are: drying temperature is 60-80°C, and drying time is 8-12h.
8. The preparation method according to claim 1, characterized in that: In step five, the heating rate is 10°C / min, the hydrogen reduction condition is 100-200°C for 2h, and the N2 calcination condition is 450-500°C for 2h.
9. A polyionic liquid-derived carbon-coated metal catalyst prepared according to the preparation method of any one of claims 1 to 8.
10. Use of the polyionic liquid derived carbon-coated metal catalyst as claimed in claim 9 in the catalytic hydrogenation reaction of chloronitrobenzene.
Citation Information
Patent Citations
Method for preparing chloroaniline through selective hydrogenation of nitrochlorobenzene
CN113292437A
Polypyrrole-derived carbon-coated metal catalyst as well as preparation and application thereof
CN117427632A
Polymer particle dispersion, electrolyte, and cell
JP2004256711A